2019
DOI: 10.1080/16549716.2019.1614371
|View full text |Cite
|
Sign up to set email alerts
|

European aid and health system strengthening: an analysis of donor approaches in the DRC, Ethiopia, Uganda, Mozambique and the global fund

Abstract: Background: In the field of international health assistance (IHA), there is a growing consensus on the limits of disease-specific interventions and the need for more health system strengthening (HSS). European donors are considered to be strong supporters of HSS. Nevertheless, little is known about how their support for HSS translates into concrete policies at partner country level. Furthermore, as development cooperation is a shared policy between the EU and its Member States, it remains unclear to what exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Considering the position of development partners with respect to health financing, poor accountability for large sums of money involving the Ministry of Health has led to important changes in the form of support for health initiatives. 56 During the late 2000s, a shift occurred from budget support to vertical programs with poor coordination and weak system strengthening. 42 Nonetheless, programmes and initiatives driven by development partners continue to play a central role for healthcare financing and services provision.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the position of development partners with respect to health financing, poor accountability for large sums of money involving the Ministry of Health has led to important changes in the form of support for health initiatives. 56 During the late 2000s, a shift occurred from budget support to vertical programs with poor coordination and weak system strengthening. 42 Nonetheless, programmes and initiatives driven by development partners continue to play a central role for healthcare financing and services provision.…”
Section: Resultsmentioning
confidence: 99%
“…A survey initiated by the European Society of Gastrointestinal Endoscopy (ESGE) revealed a general shortage of medical and nonmedical personnel in African countries. While in Europe, 1,286–6,645 physicians per million inhabitants are available, in Africa, 14–1,192 medical doctors support the medical system [113]. In parallel, academic and nonacademic training centers for basic or advanced endoscopy exist in only half of African countries [113].…”
Section: Health-care Systemmentioning
confidence: 99%
“…While in Europe, 1,286–6,645 physicians per million inhabitants are available, in Africa, 14–1,192 medical doctors support the medical system [113]. In parallel, academic and nonacademic training centers for basic or advanced endoscopy exist in only half of African countries [113]. National endoscopy societies are only known to exist in South Africa, Nigeria, Morocco, Ivory Coast, and Burkina Faso.…”
Section: Health-care Systemmentioning
confidence: 99%
“…Thus, while the NMFA's policies primarily focus on dedicating multilateral funding channels to HSS, SRHR partnerships bring their unique health system focus and localised approach to HSS and UHC. Earlier studies have indicated that if European donors like the NMFA want to ‘walk their talk’ on HSS, they will have to adjust their health development programmes and adopt innovative ways of supporting HSS (Steurs, 2019, p. 10). HSS will likely have a prominent place on the global health policy agenda until at least 2030 (Naimoli et al, 2018).…”
Section: Discussionmentioning
confidence: 99%